A Pressure Sensitive Occlusal Contact Indicator for Implant Restorations: An Observational Clinical Evaluation - Philip Millstein; Carlos E. Sabrosa; Wai Yung (Journal of Dentistry And Oral Implants, 2022)
Contact intensity is a significant factor in immoveable implant restorations. This study visually compares the use of four occlusal contact indicators one of which measures contact intensity and surface area in a single subject. The need for an occlusal contact indicator that can be used with fixed implant restorations is examined. Three contact indicators used in practice are visually compared to a novel system where pressure sensitive information and surface area can be evaluated numerically and stored. Findings suggest that intensity and surface area should be measured upon implant placement. Limitations of this observational study are discussed. Directions for future research and more systematic study are offered
Keywords: Occlusion